2019
DOI: 10.5334/tohm.481
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Primary Orthostatic Tremor Using Perampanel

Abstract: Background: Primary orthostatic tremor (POT) remains a therapeutic conundrum. Various medication classes have been tried, yielding modest results at best. Case Report: A 62-year-old female with a 13-year history of POT, refractory to clonazepam up to 20 mg/day, was treated with perampanel 1-2 mg/day. She reported 90% subjective symptomatic improvement. Discussion: This case highlights the potential for use of perampanel, a novel AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) receptor antagonist fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…In humans, several case reports have demonstrated perampanel to have a tremorolytic effect on POT 4–6 . Two main studies have been conducted on the use of perampanel for ET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, several case reports have demonstrated perampanel to have a tremorolytic effect on POT 4–6 . Two main studies have been conducted on the use of perampanel for ET.…”
Section: Discussionmentioning
confidence: 99%
“…Drug treatment for essential tremor (ET) is often unsatisfactory and more treatment options are clearly needed 1 . Perampanel, licensed and marketed as an antiepileptic drug that blocks glutamate‐mediated postsynaptic excitation, has shown efficacy in pilot studies of ET and in primary orthostatic tremor (POT) 2–6 . However, in a recent study evaluating perampanel for POT, it was observed that, although therapeutic efficacy was very high in the early weeks of treatment, the benefit failed to persist in ~50% of patients by ~3 months of treatment 6 .…”
mentioning
confidence: 99%
“…Clonazepam can result in excessive sedation and depression. A few clinical trials of gabapentin have shown it to be useful in OT with a reduction in amplitude and postural sway from 71 to 79% [73][74][75] Perampanel: There have been three case reports of perampanel resulting in marked improvement in symptoms of OT [76][77][78]. Two reports using lower doses of perampanel did not find any electrophysiological evidence of improvement [76,77] and one report using 4 mg perampanel found electrophysiological evidence of improvement [78]…”
Section: Orthostatic Tremormentioning
confidence: 99%
“…Recently, it has been reported complete resolution of POT symptoms in two patients using low doses of perampanel, an antiepileptic drug that blocks glutamate-mediated postsynaptic excitation. 4,5 In the current study, we describe our experience of using perampanel in 20 patients with POT. Although ours was not a controlled trial, our findings and conclusions may be of interest due to the low prevalence of this disorder.…”
Section: Introductionmentioning
confidence: 99%